Patrimônios de Maria: registro de fotografias digitais para salvaguardar informações do patrimônio arquitetônico da cidade de Santa Maria na web 2.0 com softwares livres - Baisch, Lucas Figueiredo (2012)
This dissertation aims to safeguard the information about the architectural patrimony in Santa Maria, a city in Rio Grande do Sul State. With this objective it was developed and implemented a systematic methodology to register and publish digital photos on the internet using free license software, what was done with the building of a website named Patrimônios de Maria , which is the result of this work done during a professional master s course. The solutions to this problem go through architectural photography, archival functions description and dissemination and the electronic document management with the use of Content Management System. It was concluded that the file format of digital photography used on the website should be: JPEG for visualizing, TIFF for downloading and RAW for backing up files. The isn t any prior direction on digital technique or framing of pictures, since all photographs, over the years, become a patrimony themselves. In addition to this it was concluded that the Norma Brasileira de Descrição Arquivística (Standard Rules for Archival Description) fits the description of architectural patrimony photographs of Santa Maria, since the collection created belongs to the Arquivo Histórico Municipal de Santa Maria ( Municipal Historic Archive of Santa Maria), that uses the same standard rule in its collection. Similarly, the website Wordpress has been shown more suitable for disseminating information because it has more applications and developers available. Finally Patrimônios de Maria becomes a knot on the internet for comunication about the architectural patrimony in the city of Santa Maria and it is a foundation that supports other media.